NEMO v4.2 eORCA1 data with RIS, FRIS and LCIS explicit ... - Hutchinson, Katherine; Deshayes, Julie; Éthé, Christian; Rousset, Clement; De Lavergne, Casimir; Vancoppenolle, Martin; Jourdain, Nicolas C.; Mathiot, Pierre (Zenodo, 2023)
PROJECT OPEN https://www.katofthesea.com/project-open OBJECTIVES As a first step towards better representing AABW source waters in NEMO global ocean 1° (eORCA1), we explicitly simulate circulation beneath Filchner-Ronne (FRIS), Larsen C (LCIS), and Ross (RIS) ice shelves. These ice shelves were chosen due to their role in the formation and setting of properties of the parent waters of AABW. METHODOLOGY NEMO version 4.2 Beta Forced with 2 cycles of CORE forcing for a reference “Closed” cavity run and an “Open” run with FRIS, LCIS and RIS represented. Inform initial conditions using an idealized regional configuration of each ice shelf. PROVIDED HERE: NAMELISTS: - NEMO reference namelist (namelist_ref; also available with NEMO code), OPEN configuration (namelist_core_ia_cfg) namelist and sea ice namelists (namelist_ice_ref and namelist_ice_cfg). Unless stated otherwise in the “cfg” namelist, the simulation uses the namelist choices provided in the “ref” namelist. The namelist_core_ia_cfg is a namelist specific ...